Prevention of child sexual abuse as from the promotion of sexual health - Villegas Ramírez, Anaid Amira (2020)
The present work carries out an intervention with girls and boys for the teaching of strategies for the prevention of Child Sexual Abuse (ASI), the promotion of their sexual health and the ability to develop self-care practices. The work was implemented in a primary school in the Valles region of Ameca, Jalisco, with the participation of female and male students aged 6 to 12, with an evaluative sample of 24 children, using the Coletas and Verdi evaluation tool. de Rodríguez and de la Cruz, 2013.The results confirm the importance of the prevention of ASI, even with protective factors that are practiced, but contrasting with the fact that children do not know essential aspects of sexuality, the ASI and caring for the body.